2011
DOI: 10.2166/nh.2011.064
|View full text |Cite
|
Sign up to set email alerts
|

Velocity profiles assessment in natural channels during high floods

Abstract: The accuracy of three different approaches for velocity profiles assessment during high floods, when the velocity points sampling is carried out only in the upper portion of the flow area, has been investigated. The first two methods assume the classical logarithmic law with additional terms, to take account of the dip-phenomenon in the velocity profile. The third one is based on the entropy theory and uses the maximum flow velocity occurring in the flow area. A sample of velocity measurements carried out at P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…In this context, to carry out new velocity measurements is feasible. In fact, on the one hand, the sampling of umax only is not costly, considering that umax occurs in the upper portion of the flow area [7] and, on the other hand, the hydraulic radius, RH, can be easily computed if the geometry of river section is known. Therefore, in order to verify the possibility of assessing Φ from α values, a backwards-testing procedure is considered.…”
Section: Estimation Of φ On the Basis Of A Historical Sample Of Convementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, to carry out new velocity measurements is feasible. In fact, on the one hand, the sampling of umax only is not costly, considering that umax occurs in the upper portion of the flow area [7] and, on the other hand, the hydraulic radius, RH, can be easily computed if the geometry of river section is known. Therefore, in order to verify the possibility of assessing Φ from α values, a backwards-testing procedure is considered.…”
Section: Estimation Of φ On the Basis Of A Historical Sample Of Convementioning
confidence: 99%
“…Entropy theory [4] shows that umax is strictly linked to the mean flow velocity, um, through a linear entropic relationship based on a single parameter, M, which is a characteristic of the gauged river site in particular [5,6], and also of the river in general [7]. Therefore by sampling umax, the information on um (and hence on discharge) can be inferred also for high flows in situations where the flow area is known.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, based on field data it is shown in several papers that the surface velocities can be properly approximated through functions such as a parabola or an ellipse. Moramarco et al [27,35] justified the validity of these equations for fitting the surface velocities through the Chezy's formula. Specifically, in this study the following functions are used: (a) parabolic function type 1: two parabolas are drawn, the vertex of both coinciding with the only point of measurement and passing through the left and right banks; (b) parabolic function type 2: two parabolas are drawn, with their vertices on the banks and each passing through the point of measurement of the maximum velocity; (c) elliptic function: two branches of an ellipse are drawn, both passing through the point of measurement of the maximum velocity and through the banks; (d) cubic function: two cubic parabolas are drawn, with their vertex on the banks and both passing through the only available point of measurement.…”
Section: Methodsmentioning
confidence: 98%
“…Equation (6) thus has validity on the y-axis, but different authors [25][26][27][28] have shown that it is reasonable in practical applications to extend this profile to the generic vertical of a cross-section without having to rely on Equation (5) for the assigned z.…”
Section: The Entropy Methodsmentioning
confidence: 99%
“…O primeiro tipo são os modelos que usam medidas de velocidades ou vazões. Eles requerem menos informações de batimetria, mas necessitam de informações de vazões e da seção para ajustar os parâmetros do modelo (CORATO et al, 2011;MORAMARCO et al, 2011). Informações de velocidades podem ser empregadas para este fim, mas deve-se considerar um perfil de velocidades para estimar a vazão (CHOO et al, 2013(CHOO et al, , 2014.…”
Section: Introductionunclassified